METODE DAKWAH MELALUI SYAIR BURDAH - Mochammad Irfan Achfandhy (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2020)
Burdah is a poetry that has been phenomenal, especially in Indonesia. These poems by Imam al-Bushiri have been composed into various songs accompanied by musical accompaniment. The beautiful chanting of Burdah syair is used as a form of preaching in various assemblies, especially in the Majelis Sholawat Wat Ta’lim Sholawat Burdah Ponorogo City. This study aims to describe and observe the da'wah methods implemented in the Majelis Sholawat Wat Ta'lim Sholawat Burdah. This research approach uses qualitative descriptive. The results showed that from various series of activities the implications of the da'wah method included the bil-hikmah and mauidzatil hasanah methods. Apart from that, the Burdah sholawatan syair was chosen to support its attractiveness and adjust the trends or fashions in the current era, especially the majority of young people so that the enthusiasm of the congregation will increase.